Legal Frameworks for Heritage Protection in Nepal: Review from Legal Pluralism Perspective - Kharel, Amrit (Nepalese Culture, 2025)
Nepal’s monuments and archaeological sites are crucial cultural assets representing its historical legacy and national identity. However, their protection faces significant challenges due to gaps in the legal framework, weak enforcement, and minimal community participation. This study critically analyzes Nepal’s constitutional provisions, legislations, international legal obligations, and landmark judicial precedents set in the relevant case laws to identify shortcomings in the current approach to heritage protection. This paper is guided by theoretical perspective of legal pluralism. The research paradigm is interpretivism and the study uses qualitative research design with a hermeneutics textual analysis method for the review of the existing policies, legal frameworks and judicial trends to assess the adequacy of existing laws. Major issues identified include insufficient legal provisions for local community involvement, inadequate disaster resilience strategies, and limited collaborations between public and private sectors. The study recommends strengthening the legal framework by introducing the new comprehensive legislation on monumental and archeological heritage protection. Further the paper suggests to amend other relevant acts to promote community engagement through workshops, financial incentives, and training on heritage value, and fostering public-private partnerships for funding and technical support. In conclusion, protecting Nepal’s heritage sites requires a collaborative effort involving the government, local communities, and international partners to ensure sustainable management and effective implementation of legal provisions based on legal pluralism.